Anomalous Renal Effects of Tin Protoporphyrin in a Murine Model of Sickle Cell Disease - Juncos, Julio P. (American Society for Investigative Pathology, 2006)
In human and murine models of sickle cell disease (SCD), heme oxygenase-1 (HO-1) is induced in the kidney, an organ commonly involved in SCD. The present study assessed the role of HO-1 by using a competitive inhibitor of HO activity, tin protoporphyrin (SnPP), in protocols affording a composite, clinically relevant analysis of the kidney in SCD under unstressed and stressed conditions. Whereas short-term administration of SnPP exerted comparable renal hemodynamic effects in wild-type and sickle mice, chronic administration of SnPP exerted divergent effects: SnPP provoked tubulointerstitial inflammation and up-regulation of injury-related genes in wild-type mice, whereas in sickle mice SnPP reduced expression of injury-related genes and vascular congestion without provoking tubulointerstitial inflammation. SnPP also protected against the heightened sensitivity to renal ischemia observed in sickle mice, preventing ischemia-induced worsening of renal injury in sickle mice above that observed in wild-type mice. Effective and comparable inhibition of HO activity by SnPP in wild-type and sickle mice was confirmed. These findings suggest that induction of HO-1, at least as assessed by this approach, may contribute to renal injury in this murine model of SCD and uncover an experimental maneuver that protects the kidney in murine SCD.